Chemical composition and antibacterial activity of seven uncommon essential oils. Issue 4 (4th July 2018) - Rosato, Antonio; Maggi, Filippo; Cianfaglione, Kevin; Conti, Fabio; Ciaschetti, Giampiero; Rakotosaona, Rianasoambolanoro; Fracchiolla, Giuseppe; Clodoveo, Maria Lisa; Franchini, Carlo; Corbo, Filomena
Abstract: Seven uncommon types of essential oils obtained from Pinus nigra, Hyssopus officinalis, Sison amomum, Smyrnium olusatrum, Helosciadium nodiflorum, Pelargonium graveolens and Vepris macrophylla were tested against a panel of thirty bacterial strains that cause serious infectious diseases. Among these bacterial species, the most dangerous for human health were five documented multi-drug-resistant strains belonging to the Acinetobacter and Klebsiella genera and derived from clinical isolation. The chemical composition of essential oils was achieved by GC-MS analysis, whereas the antibacterial efficacy was evaluated by the microdilution technique according to CLSI document M7-A9. The Vepris macrophylla essential oil, which contains geranial (33.2%), neral (23.1%) and citronellol (14.5%), exhibited the strongest inhibition against the multi-resistant strains A. baumannii, K. pneumoniae and S. aureus, with MIC values of 4.1, 2.05 and 4.1 mg/ml, respectively.